Fiona Candlin, Micromuseology: An Analysis of Small Independent Museums, Bloomsbury: London, 2016, paperback £28.99, pp. 224 - Quigley, Oonagh (Museum and Society, 2018)
This book is the first to tackle micromuseums from an academic viewpoint. Previous approaches to small museums have generally been from a practical perspective (Catlin-Legutko and Klinger 2011), or written for a lay audience (Davies 2010; Redington 2002). Micromuseums are generally considered to be small, single-themed and independent institutions.